58.6k views
1 vote
If F is the midpoint for EG then, x = ?

EF = 6x - 4
FG = 5x + 7

please show your work!

User SajithK
by
5.8k points

2 Answers

4 votes
I hope this helps you



EF=FG



6x-4=5x+7



x=11
User Wolfgang Leon
by
6.2k points
2 votes

Answer:

x=11

Explanation:

If F is the midpoint for EG, then the length of EF and FG are same

F is a midpoint for EG , so EF = FG4


EF = 6x - 4, FG = 5x + 7

LEts replace EF and FG


EF = FG


6x-4= 5x+7, solve for x

Subtract 5x on both sides


6x-5x-4= 5x-5x+7


x-4=7

Add 4 on both sides

x=11

The value of x= 11

User Rames
by
7.0k points